Comparison of cardiovascular disease risk factors among FiLWHEL (2014-2016), NNS (2013) and KNHANES (2013-2015) women - Sherlyn Mae P. Provido; Grace P. Abris; Heejin Lee; Akinkunmi Paul Okekunle; Glen Melvin Gironella; Mario V. Capanzana; Grace H. Chung; Sangmo Hong; Sung Hoon Yu; Chang Beom Lee; Jung Eun Lee (BMC, 2023)
Abstract Objectives This study assessed the CVD risk factors among Filipino women (FW) in Korea and compared them with FW in the Philippines and women in Korea (KW). Methods A cohort of 504 women from the Filipino Women's Health and Diet Study (FiLWHEL) aged 20-57 years old were age-matched (1:1 ratio) with women from the 2013 National Nutrition Survey in the Philippines and the 2013-2015 Korean National Health and Nutrition Examination Survey. Anthropometric data, blood pressure (BP), lipid and glucose levels were compared across the four populations by calculating the odds ratio (OR)s and 95% confidence interval (CI)s using conditional logistic regression models. Results Compared to KW, FW in Korea and FW in the Philippines were more than 2 and 3 times higher odds of having obesity for BMI ≥ 30 kg/m2 and waist circumference ≥ 88 cm, respectively. However, FW in Korea had the highest odds (OR 5.51, 95% CI 3.18-9.56) of having hypertension compared to KW. FW in the Philippines had the highest odds of having dyslipidemia (compared to KW, total cholesterol ≥ 200 mg/dL: OR 8.83, 95% CI 5.30-14.71; LDL-C ≥ 130 mg/dL: OR 3.25, 95% CI 2.13-4.98; and triglyceride ≥ 150 mg/dL: OR 2.59, 95% CI 1.59-4.22), but FW in Korea and KW had similar prevalence of dyslipidemia. Conclusions FW in Korea had higher prevalence of obesity and hypertension, with similar prevalence of dyslipidemia compared to KW in this sample. FW in the Philippines had higher prevalence of dyslipidemia compared to FW in Korea. Further prospective studies are warranted to examine the CVD risk factors among continental and native-born Filipino women.